2013
DOI: 10.12989/ose.2013.3.3.219
|View full text |Cite
|
Sign up to set email alerts
|

Influence of viscous effects on numerical prediction of motions of SWATH vessels in waves

Abstract: The accurate prediction of motion in waves of a marine vehicle is essential to assess the maximum sea state vs. operational requirements. This is particularly true for small crafts, such as Autonomous Surface Vessels (ASV). Two different numerical methods to predict motions of a SWATH-ASV are considered: an inviscid strip theory initially developed at MIT for catamarans and then adapted for SWATHs and new a hybrid strip theory, based on the numerical solution of the radiation forces by an unsteady viscous, non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…We agree with him that the viscous effects are very relevant for the prediction of SWATH vertical motions and should be always included if the final scope of the study is the exact prediction of motions in waves. In fact, using a unsteady viscous flow solver, for a different type of SWATH (Brizzolara et al, 2013), we recently demonstrated that it is not possible to get a reliable prediction of heave and pitch responses if viscous forces are not included in the estimation of the radiation forces. Additional references on this theme and on the fully non-linear viscous flow solver that we have adapted to the scope are added here (Bonfiglio & Brizzolara, 2013;Bonfiglio & Brizzolara, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We agree with him that the viscous effects are very relevant for the prediction of SWATH vertical motions and should be always included if the final scope of the study is the exact prediction of motions in waves. In fact, using a unsteady viscous flow solver, for a different type of SWATH (Brizzolara et al, 2013), we recently demonstrated that it is not possible to get a reliable prediction of heave and pitch responses if viscous forces are not included in the estimation of the radiation forces. Additional references on this theme and on the fully non-linear viscous flow solver that we have adapted to the scope are added here (Bonfiglio & Brizzolara, 2013;Bonfiglio & Brizzolara, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Hydrodynamic forces are predicted by the inviscid BEM without correction for viscous effects of any kind. If this is not a drastic approximation in case of conventional monohulls and catamarans (Bonfiglio & Brizzolara, 2013), in case of SWATHs viscous radiation forces were proven to affect the amplitude of the response, particularly around the resonance frequency (see for instance Brizzolara et al, 2013 andCenteno et al, 2000).…”
Section: Motions In Wavesmentioning
confidence: 99%
“…Close to resonance, viscous and non-linear free surface effects are heavily affecting added mass and damping forces. The exact estimation of these forces is essential to obtain reliable motion predictions, as demonstrated in [18] by means of the viscous strip theory, previously mentioned.…”
Section: Figure 9 -Vortex Shedding In Heave Oscillations Predicted Fo...mentioning
confidence: 99%
“…The relevance of viscous effects for the accurate prediction of SWATH motions in regular and irregular waves was addressed in [18], where the added mass and damping of the 3D ASV-SWATH hull were calculated and compared with a potential flow based strip theory developed years ago at MIT [19]. Motions evaluated with the viscous method result considerably different from the pure potential ones: around the first resonance mode (piston model frequency) the calculated differences are 20% on the heave amplitude and 50% on the pitch amplitude.…”
Section: Figure 9 -Vortex Shedding In Heave Oscillations Predicted Fo...mentioning
confidence: 99%
See 1 more Smart Citation